Effectiveness of Blended Learning Model Assisted By Scholoogy to Improve Language Skills of Early Childhood Education Teachers - Sukini Sukini; Embang Uluk; Nieke Masruchiyah; R. Nurhayati4; Muh. Safar; Ika Agustina; Windy Dian Sari; Tomi Apra Santosa (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the influence of the Scholoogy-assisted blended learning model on improving language skills in prospective early childhood education teachers. This study is a quantitative research with a meta-analysis approach. The inclusion criteria in this study include a) research obtained through the Google Scholar database; DOAJ, ScienceDirect; Wos and Wiley, b) research must be indexed by the Science Technology and Index (SINTA), Web of Science or Scopus; c) the research topic must be relevant; d) the research was published in the 2021-2024 range; e) Research sample > 30 students. Analyze data with the help of JSAP applications. The results of this study concluded that the 23 studies analyzed obtained an effect size value (d = 1,081; Z = 9.685; p < 0.001) is included in the very high effect size category. These findings show that the Scholoogy-assisted blended learning model greatly affects language skills in early childhood education students. In addition, the application of the blended learning model assisted by schology is effective in helping to develop students' language skills in learning. This research is expected to contribute to the world of education and research in the future.